PENGARUH KUALITAS LAYANAN, PERSEPSI HARGA DAN CITRA PERUSAHAAN TERHADAP KEPUASAN PELANGGAN PUSAT KEBUGARAN WANITA (Studi Pada Pelanggan Em Studio Senam Semarang) - Ulfatul Jannah, 14.05.51.0237; Widyasari, Suzy (Students' Journal of Economic and Management, 2019)
The purpose of this study is to analyze the effect of service quality, perceived value, and corporate image on customer satisfaction of womens fitness center at Em Studio Senam Semarang. Population in this research is customers who have been member for at least 3 months at Em Studio Senam Semarang. The number of samples studied is as many as 100 respondents sampling technique by purposive sampling. Data testing techniques used include validity test with factor analysis, reliability test with alpha cronbach, classic assumption test. The results in this study indicate that service quality has not significant effect on customer satisfaction, perceived value has significant effect on customer satisfaction, and corporate image has not significant effect on customer satisfaction. The variable that has the most influence on the customer satisfaction is the perceived value followed by corporate image and service quality.